TEACHING ENGLISH THROUGH DRAMA: A HISTORICAL PERSPECTIVE - Wiwoho, Gurendi (LINGUAMEDIA Journal, 2023)
This paper tries to discuss about the importance of using drama as a tool to teach English from historical background. The discussion starts with the use of drama in education and and the role of teacher and drama play. Ghe concepts of theatre is also explored theoretically based on slme experts. Finally, some approaches to learning through drama are discussed. In conclusion,  using drama in English teaching provides an interesting alternative to foster students' English ability creatively, communicatively and successfully Keywords: teaching English, drama, teacher’s role